Dependency association of determinants of uptake of loans «drop by drop» in micro, small and medium enterprises - Barrera Lievano, Jhony Alexander (2022)
The main objective of this study is to determine if there is a dependency association between the characteristics of micro, small and medium-sized companies - MSME, in terms of size, seniority, level of education of their managers and their gender, and the taking of credit drop by drop. An investigation is developed with quantitative methodology and the population under study is taken as MSME of a capital city of Latin America. As the main findings, it is identified that there is a dependency association between the variables of company size, company age, level of education of the manager, and take credit drop by drop.